The protracted neurotoxic consequences in mice of developmental exposures to inhaled iron nanoparticles alone or in combination with SO2 - Cory-Slechta, Deborah A.; Marvin, Elena; Welle, Kevin; Oberdörster, Gunter; Sobolewski, Marissa (Frontiers in Behavioral Neuroscience, 2025)
IntroductionAir pollution (AP) has been associated with increased risk for multiple neurodevelopmental disorders. As one of the most abundant contaminants of AP, iron (Fe) is critical to brain function, with both deficiencies and excesses leading to potential neurotoxicity. Our prior studies examining the impact of developmental exposures of mice to inhaled Fe (1.0 μg/m3) alone or in conjunction with sulfur dioxide SO2 (1.31 mg/m3; FeS) from postnatal days (PND) 4–7 and 10–13 (human 3rd trimester brain equivalent period) revealed alterations in brain neurotransmitter levels at PND14 which had generally recovered by PND60, but which were, nevertheless, followed by behavioral impairments. The current study sought to determine whether subsequent behavioral experience, which requires neurochemical mediation, had unmasked residual deficits in neurotransmitter function in response to developmental FeS or Fe inhalation.MethodsConsequently, levels of brain neurotransmitters and trans-sulfuration markers were measured in mice that had either behavioral experience (BE) or no behavioral experience (NB) at PND 215 (Fe only) or 357 (FeS).ResultsBE itself markedly increased brain neurotransmitter and trans-sulfuration marker levels, particularly in males. These increases were prevented in males in both frontal cortex and striatum by prior developmental FeS exposures. In females, developmental Fe exposure was associated with residual increases particularly in striatal serotonergic function and levels of homocysteine independently of behavioral experience.DiscussionCollectively, these findings show the ability of behavioral experience to unmask later life residual consequences of developmental exposures to FeS in males and of latent emerging effects of Fe in females. The collective findings may have relevance to later life neurodegenerative diseases and disorders now increasingly associated with air pollution exposures, and also underscore how understanding how various components of air pollution influence brain is critical to regulatory decisions for public health protection.